The Association Between Exposure to Cigarette Smoke in Pregnant Women and Estimated Foetal Weight in Kepahiang Regency - Putri Utami (Jurnal Kesehatan, 2025)
Introduction: Infant mortality rate serves as a critical indicator in assessing population health, reflecting the overall well-being of a community. Foetal development is influenced by multiple determinants, including maternal health, foetal factors, and environmental conditions. When pregnant women are exposed to cigarette smoke as passive smokers, the toxic chemical constituents present in tobacco smoke can disrupt pregnancy outcomes. An early detection method to evaluate foetal growth involves estimating foetal weight through clinical examination. Method: This study aims to analyse the characteristics of pregnant women exposed to secondhand smoke in relation to estimated foetal weight in Kepahiang Regency. This research employs an observational analytic design with a cross-sectional approach. Data were collected through structured questionnaires and uterine fundal height measurements, with a total sample size of 72 pregnant women. Results: The analysis revealed no statistically significant association between household cigarette smoke exposure (p = 0.722), duration of secondhand smoke exposure (p = 0.497), or urinary cotinine levels (p = 1.000) and estimated foetal weight. Conclusion: These findings suggest that maternal exposure to secondhand smoke may not necessarily influence estimated foetal weight, as other confounding factors could play a more dominant role in foetal growth.